AÇÕES DE MARKETING EM INSTITUIÇÕES DE ENSINO SUPERIOR: UM ESTUDO NA REGIÃO DO GRANDE ABC - Eduardo Linzmayer; Sílvio Augusto Minciotti (Revista Gestão Universitária na América Latina, 2017)
The Educational Marketing is an important activity that has been used as a differential factor services by higher education institutions (HEIs) from Brazil. This research identified and analyzed the current actions and marketing practices of 33 institutions working in the Greater ABC region, and they have evolved with reference to two studies previously conducted by Martins (1986) and Bittencourt (2005). The methodology used for this stud y was based on three stages, a first corresponding to a literature based on studies, a second exploratory through semi - structured interviews and the descriptive and third census based on responses from questionnaires sent to the educational institutions un der study. In the field research, which began in late 2014 and completed in 2015, found to be sensitive changes in the practice of Educational Marketing, especially in relation to the professionalization of the responsible managers and consolidation of the area of communication and marketing in the surveyed institutions. It found also that HEIs are increasingly investing their resources to attract students considering opening new institutions, new courses and increase the number of vacancies that exist in m ergers and acquisitions, which have their vacancies fulfilled. At the end of the survey were registered comparisons across the three studies in 1986, 2005 and 2015 this where these aforementioned changes and the growing importance and adoption of the Educa tional Marketing as an important factor of changes in education services, teaching and research were found offered by IES.